Plan de comunicación para la Universidad Politécnica Salesiana : Sede Quito. - Nacimba Ortíz, Andrea Vanessa (2012)
This project involves performing a proposed Communication Plan for the Salesian Polytechnic University, Quito headquarters. The main feature for this project was the need to make fundamental, that a communication plan should be seen as a basic tool and transcendental in all entities.